Synaptosomal signal transduction in Alzheimer's disease - Coelho, Edgar Duarte de Jesus Valente Marques (2011)
Alzheimer’s Disease (AD) is characterized by the presence of amyloid plaques (APs) and neurofibrillary tangles (NFTs), which consist of Abeta aggregates and hyperphosphorylated tau, respectively. It is known that increasing Abeta concentrations precede NFT production. Moreover, several lines of evidence suggest that the increase in APP and tau phosphorylation is the result of Abeta neurotoxicity. Although, the precise effects of the neurotoxic peptide on APP and tau phosphorylation remain yet to be fully elucidated. Synapses exhibit high concentrations of protein kinases (PKs) and protein phosphatases (PPs). Therefore, it is essential to adopt a model system that mimics what happens at the synapse. Synaptosomes are actually recognized as “in vitro synapses” and for that reason were the model system used. Our data revealed that there was a considerable enrichment of pre- and postsynaptic markers in the synaptosomal fraction after synaptosome isolation. Given these results, we went on to test the effects of Abeta on synaptosomal viability, which was found to be slightly decreased, confirming the high viability of synaptosomes. In addition, we observed the increase of APP and tau phosphorylation after Abeta treatment, while holo-APP and total tau levels were maintained, independently of Abeta concentrations. These results suggest that Abeta can actually induce APP and tau hyperphosphorylation. The conclusions attained from this dissertation are important to comprehend the pathways related to the pathogenesis of Alzheimer’s disease.